Uso de Drogas durante el Embarazo Hospital II Integrado IPSS – Tarapoto 1992. - Panduro Torres, lrma (1993)
The advancement of technology determines the pharmacological drug therapy becomes decreasing importance in the practice of obstetrics. Progress in perinatológica branch evolution of drug use and other drug discovery make it necessary for the professional in the field of obstetrics has knowledge about their use and the implications of these in pregnancy and problems such as induction of abortion, threatened abortion, hyperemesis, preterm birth, infections, hypertensive disorders among others. Many researchers have found that pregnant women take a surprising amount of drugs, although they are aware of ceratogénico potential. On the other hand studies report that most drugs taken in the latter half of pregnancy and there is relatively limited in the first quarter. The drugs most frequently used are the analgesics, antacids, sedatives and drugs to treat infections. There is also a tendency to believe that most of the drugs used by pregnant women are taken without proper prescription generates an indiscriminate use of drugs in our environment is not yet known. Hospital-based retrospective studies that estimate the amount of drugs to which women are exposed during pregnancy. Pharmacy records (rather poor in our midst) and data from hospital records must develop prospective studies in order to determine the prevalence of drug use. Farfan and Nelson found that 83% of 911 unselected pregnant women received prescription drugs and medical exposure to drugs was three per patient (2).